Economic viability and cost-benefit analysis of community-based ecotourism service provider in Kubang Kerian, Kelantan, Malaysia - Abdullah, Siti Mariam Mellisa (2019)
Like other natural resource-endowed developing economies, Malaysia has been aggressively boosting ecotourism as a subset of the tourism industry. It has become apparent in recent years that ecotourism in this country is gaining acknowledgement, mainly due to growing global awareness of sustainability and environmentalism. One of the new forms of ecotourism product is community-based ecotourism which is involved and managed locally by the communities in its development and management; and substantial benefits remain within the community. This study has been conducted in the village of Min House Camp (MHC), Kelantan to assess the economic viability and costbenefit analysis of community-based ecotourism service provider. For the first objective, a survey from 200 responses from different stakeholders in MHC using partial least square structural equation modelling were used to identify the attitudes of relevant stakeholders and their perceptions in support of CBE development.For the second objective, a survey of 360 local and international visitors were collected using choice experiment to assess the economic value for each improvement attribute for conservation and management. For the third objective, the aim was to formulate and assess the feasibility of alternative options of community-based ecotourism project at MHC, Kelantan using the cost-benefit analysis. Two scenarios are evaluated: first ‘without project’, which reflects the status quo whereby community participation and ecotourism activities are excluded, and this serves as the base case for assessing the difference in project options, and, second ‘with ecotourism project’ in MHC. By using the partial least squares-structural equation modelling method, findings revealed that stakeholders' support for community-based ecotourism development is a function of perceived benefits and perceived cost of tourism impacts and three exogenous variables of stakeholders’ involvement, knowledge of ecotourism, and environmental attitudes. For the indirect relationship, it shows the three exogenous variables has an indirect relationship with stakeholders’ support for community-based ecotourism development through mediating variables of perceived benefits and costs. However, the knowledge of ecotourism is the most influential factor to support community-based ecotourism development in MHC. This shows key stakeholders that involved in the management must possess sufficient knowledge in ecotourism to provide the directions needed to carry out proper planning for community-based ecotourism. The business operator should understand the importance of perceived benefits and costs of CBE as this construct has a strong influence to support CBE development in MHC. For the choice experiment method, the study measures the economic value of ecosystem services offered by community-based ecotourism by assessing the willingness to pay for various intangible ecotourism services offered by the community-based ecotourism provider at MHC, Kelantan. The results show the conditional logit interaction model were best fitted model as visitors are mostly willing to pay a significantly higher price for improved conservation and management attributes. In terms of conservation issues, visitors are willing to contribute the most on ‘fair’ ecological management as the important attribute, followed by ‘stop’ declining the number of unfamiliar local and exotic animal species observation’ and ‘fair’ ecological management. The marginal values for each improvement attribute were RM18.05, RM19.36 and RM20.10 respectively. In terms of management issue, visitors are willing to contribute the most on the ‘super’ package activity attribute, followed by ‘increase 10%’ the involvement and employment of local people, ‘medium’ information provided, and lastly ‘very good’ accommodation facilities. The marginal values for each improvement attribute were RM4.62, RM3.54, RM2.88 and RM2.02 respectively. Hence, the results of the study would enable MHC to incorporate the economic value information of ecosystem services offered in revising its pricing strategy, where eco-friendly attraction can be offered sustainably. For the cost-benefit analysis method, the study formulates and assesses the feasibility of alternative options of community-based ecotourism project at MHC, Kelantan. The responses for economic value of conservation and management attributes which were analyzed using choice experiment are then incorporated into the cost-benefit analysis of establishing a community-based ecotourism at MHC. Both net present values ‘without project’ and ‘with project’ were computed and use to estimate the incremental net present value of the community-based ecotourism at MHC. The positive incremental net present value obtained implies that the community-based ecotourism development at MHC shows a bright prospect for ecotourism with community participation. In this case, the government needs to view and consider ecotourism and conservation not as an expense, but rather generating benefits for the welfare of society so that the rural local community could gain benefits of the CBE to be shared among the communities. Finally, the above findings and their implications have some policy relevance in that the promotion of community-based ecotourism in the national tourism policy has been found to be pragmatic and workable. These findings are useful information for the policy maker, government, and tourism operators to enhance greater stakeholder participation in developing and sustaining community-based ecotourism.The results of economic valuation and cost-benefit analysis could aid the government to gain insight about real value of community-based ecotourism in support of profitable venture that incorporates ecosystem conservation. MHC at Kubang Kerian, Kelantan is such a successful model case study.